1996
DOI: 10.1074/jbc.271.41.25117
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regulation of G1 Cyclins in Oxidant-induced Growth Arrest of Lung Alveolar Epithelial Cells

Abstract: The alveolar surface of the lung is a major target for oxidant injury, and its repair following injury is dependent on the ability of its stem cells, the type 2 cells, to initiate proliferation. From previous studies it is likely that events located before the entry into the S phase of the cell cycle and involving several components of the insulin-like growth factor system as well as of transforming growth factor-␤ (TGF-␤) play a key role in growth regulation of oxidant-exposed type 2 epithelial cells. To gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 59 publications
4
61
0
Order By: Relevance
“…p21 has also been shown to play a crucial role in cell cycle control in response to the other stimuli such as glucocorticoids (22) and cigarette smoke (23). In lung epithelial cells, a marked increase in p21 has been observed after oxygen exposure (15). A study by Corroyer et al (15) found that one target of p21 action was the cyclin E-CDK2 complex that facilitates cell cycle progression to the S phase (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…p21 has also been shown to play a crucial role in cell cycle control in response to the other stimuli such as glucocorticoids (22) and cigarette smoke (23). In lung epithelial cells, a marked increase in p21 has been observed after oxygen exposure (15). A study by Corroyer et al (15) found that one target of p21 action was the cyclin E-CDK2 complex that facilitates cell cycle progression to the S phase (15).…”
mentioning
confidence: 99%
“…In lung epithelial cells, a marked increase in p21 has been observed after oxygen exposure (15). A study by Corroyer et al (15) found that one target of p21 action was the cyclin E-CDK2 complex that facilitates cell cycle progression to the S phase (15). Induction of p21 can occur via p53-dependent (24,25) and p53-independent mechanisms (26 -29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to ROS treatment, p21 has been shown to inhibit cyclin-CDK2 activity in alveolar epithelial cells and arrest the cell cycle (7). Similarly, in mice exposed to hyperoxia, there is accumulation of p21 in both the bronchiolar and alveolar epithelium that decreases over time during the recovery period (32).…”
Section: Fig 4 Western Analysis Of P27mentioning
confidence: 99%
“…The p53 pathway was found to be involved upon exposure of lung epithelial cells to either hyperoxia (Barazzone et al, 1998;McGrath, 1998;O'Reilly et al, 1998) or to a number of DNA-damaging agents and carcinogens (Corroyer et al, 1996;Fujishita et al, 1995;Gadbois and Lehnert, 1997;Guinee et al, 1996). The expression of p16 (Sabourin et al, 1998), p21 (Guinee et al, 1996;McGrath, 1998), Rb (Fujishita et al, 1995;Sabourin et al, 1998), c-jun (Dolan et al, 1994;Haase et al, 1997), c-Fos (Haase et al, 1997), TNF-a (Lee and Rannels, 1998;Yao et al, 1998), TGFh (Lee and Rannels, 1998), BAX (Guinee et al, 1997), and Bcl-2 (Guinee et al, 1997) was reported to be influenced by a number of DNA-damaging agents and pollutants but the exact mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%